The Irish Experience of Identity Representation: M. J. Hyland’s “Carry Me Down” - Drozdovskyi, Dmytro; Ivanyshyn, Petro; Prykhodko, Oksana (Journal of History Culture and Art Research, 2020)
This paper discusses the philosophical features of M. J. Hyland’s novel Carry Me Down (2006) by spotlighting the epistemological paradigm of post-postmodernism. The novel has been discussed in the paradigm of post-postmodernism taking into account the specifics of Irish novel in the second half of the 20th – early 21st centuries (anticolonial explications and the smashed type of identity of the characters). It is stated that Carry Me Down reveals the post-postmodern tendency of seeking for the truth by the protagonist (John Egan) and explaining the nature of human beings in the combination of humanitarian and biophysical. The protagonist of the story has a special superpower of detecting lie in the discourses produced by other characters. The post-postmodern feature is represented in the tendency of rejection of the hybridization between truth and untruth as John physically cannot accept lies (his body vomits and he has a physical discomfort). It was admitted that such a tendency of representing a character with unacceptable forms for lie is also represented in some other British post-postmodern texts, e.g. in The Curious Incident of the Dog in the Night-Time by M. Haddon. In general, the novel exploits the idea of a new way of thinking that can provide forms of existence in the situation of post-truth. The theories of trauma representation in contemporary fiction have been also underlined.